New species of Nothybus Rondani, 1875 (Diptera: Nothybidae) from Vietnam with a key to Vietnamese species of the genus - Galinskaya, Tatiana V.; Shatalkin, Anatole I. (Zootaxa, 2015)
This study is part of an ongoing series of studies on the Vietnamese cyclorrhaphous fauna. One new species from Vietnam, Nothybus kuznetsovorum sp.nov., is described and figured. A key to species of Nothybus is provided. Genital structures are described and figured.